2019
DOI: 10.11622/smedj.2019030
|View full text |Cite
|
Sign up to set email alerts
|

Relation of blood pressure variability to left ventricular function and arterial stiffness in hypertensive patients

Abstract: O r i g i n a l A r t i c l e METHODS Ambulatory BP monitoring (ABPM) and echocardiography were performed in 116 hypertensive patients. We assessed BP variability as standard deviations of daytime systolic BP on 24-hour ABPM. Conventional echocardiographic parameters, area strain and three-dimensional diastolic index (3D-DI) using 3D speckle tracking were measured. Arterial stiffness was evaluated by acquiring pulse wave velocity (PWV) and augmentation index. RESULTS Patients with higher BP variability showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…The present study, enrolled predominantly young and middle-age males with uncomplicated AH, demonstrated that HBPV was associated with more pronounced AH-mediated subclinical target organ damage, namely the LV mass index, carotid arteries and kidneys, which was in agreement with other available studies [12,13,[25][26][27]. Moreover, HBPV was also associated with more advanced hypertensive retinopathy, that may reflect potential pathophysiological associations of BP variability with retinal microvascular abnormalities in AH [29,30]. At the same time, the obtained results are worth consideration due to several aspects.…”
Section: Discussionsupporting
confidence: 92%
“…The present study, enrolled predominantly young and middle-age males with uncomplicated AH, demonstrated that HBPV was associated with more pronounced AH-mediated subclinical target organ damage, namely the LV mass index, carotid arteries and kidneys, which was in agreement with other available studies [12,13,[25][26][27]. Moreover, HBPV was also associated with more advanced hypertensive retinopathy, that may reflect potential pathophysiological associations of BP variability with retinal microvascular abnormalities in AH [29,30]. At the same time, the obtained results are worth consideration due to several aspects.…”
Section: Discussionsupporting
confidence: 92%
“… 32 Likewise, increased BPV has been associated with arterial stiffness and LV mass and dysfunction in treated and untreated hypertensive population, suggesting that BPV may be an important determinant of HMOD. 33 , 34 , 35 In a group of elderly hospitalized patients, 24‐h SBPV could reflect the degree of HMOD as it was associated with IMT, LVMI and MAU. 36 In a 7‐year follow‐up study of a small hypertensive group ( n = 73), Frattola et al reported that the BP level achieved by treatment, the degree of HMOD at baseline evaluation and the long‐term BPV were the most important determinants of future end‐organ damage related to hypertension throughout the years of follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…The patient cohort in this study was based on the Maastricht Study, which consists of type 2 diabetes mellitus patients, and PWV was measured to document aortic stiffness. Shin et al also reported an association between daytime SBPV and arterial stiffness, which was also documented with PWV (19). PWV measurement has several limitations, such as estimation of the length of the arterial system, estimation of a unidirectional pathway for pulse pressure to travel and close relation with instant BP and heart rate at the time of measurement (20).…”
Section: Discussionmentioning
confidence: 85%